Insights Into the Role of Matrix Metalloproteinases in Cancer and its Various Therapeutic Aspects: A Review - Mustafa, Sabeena; Koran, Sheeja; AlOmair, Lamya (Frontiers in Molecular Biosciences, 2022)
Matrix metalloproteinases (MMPs) are zinc dependent endopeptidase that regulate the turnover of extracellular matrix (ECM) components. Gross and La Piere discovered MMPs in 1962 during an experiment on tissue samples from a tadpole's tail. Several subtypes of MMPs are distinguished, depending on their substrate-specificity and localization. MMPs are involved as an essential molecule in multiple and diverse physiological processes, such a reproduction, embryonic development, bone remodeling, tissue repair and regulation of inflammatory processes. Its activity is being controlled at various levels such as transcription level, pro-peptide activation level and by the activity of a family of tissue inhibitors of metalloproteinase (TIMP) endogenous inhibitors of MMPs. Cancer metastasis, the spread of tumor to distant site, is a cascade of intertwined, interconnected, highly complicated process and the prime cause of mortality related to most cancers. It is considered to be an indicator of cancer metastasis. During metastasis the tumor cells have to invade the blood vessel and degrade the ECM to make a path to new loci in distant places. The degradation of blood vessels and ECM is mediated through the activity of MMPs. Hence the MMPs activity is critical to determine the metastatic potential of a cancer cell. Evasion of apoptosis is one of the hallmarks of cancer are found to be correlated with the expression of MMPs. As a result, given the importance of MMPs in cancer, we describe the role of these multifunctional enzymes MMPs in various aspects of cancer formation and their rising possibilities as a novel therapeutic target in this review. There is also a brief discussion of various types of therapeutic components and drugs that function against MMPs.